Development Of an Intelligent Clothes Drying System with Real-Time Monitoring and Control - Kurkure, Girish; Ramani, Shivangi (Internet of Things and Artificial Intelligence Journal, 2023)
The unpredictable climate and the increasing need for clean and dry clothes have made it challenging for individuals to perform daily tasks such as laundry. The high costs of using a laundry service and the difficulty of drying clothes outdoors or indoors make it imperative to develop an innovative solution to tackle this problem. This research proposes an intelligent IoT device that incorporates a dryer hanger with AI analytics to track the status of clothes and dry them effectively and efficiently. The device is designed to ensure safety and prevent unpleasant odors caused by mold growth and pollen. The proposed solution is particularly beneficial for individuals who are disabled or have a busy schedule as it eliminates the need to check the status of clothes being dried frequently. The device's effectiveness will be assessed by conducting experiments to evaluate its drying speed, energy consumption, and safety. The study results will provide insight into the device's feasibility and potential impact on mitigating the challenges associated with laundry tasks.